The Social Dimension of Participation and Completion in MOOCs - Valentina Goglio; Paolo Parigi (Educational Technology & Society, 2020)
The rapid and impressive development of Massive Open Online Courses (MOOCs) in less than half a decade has generated contrasting arguments about their social dimension. This paper investigates how the socio-economic background of learners affects their own experience and chances of course completion. The analyses test whether learners with a low socio-economic status (SES) have fewer chances of completing the online course and whether participation in online discussion forums moderates the role of SES. The data comes from two MOOCs provided by Stanford University. We find a negative association between low SES, course completion and course engagement. Moreover, we find that forum participation plays an ambiguous role, reinforcing the advantage of well-educated learners enrolled in one course, while it has no significant effect on the other course. The article concludes with some policy implications on social stratification in MOOCs and with some design suggestions for creators of MOOCs.